2013
DOI: 10.25077/jka.v2i2.127
|View full text |Cite
|
Sign up to set email alerts
|

Hubungan antara Proteinuria dan Hipoalbuminemia pada Anak dengan Sindrom Nefrotik yang Dirawat di RSUP Dr. M. Djamil Padang periode 2009-2012

Abstract: AbstrakSindrom nefrotik terdiri dari proteinuria massif, hipoalbuminemia, edema, serta dapat disertai hiperkolesterolemia. Proteinuria merupakan gejala utama pada sindrom nefrotik, sedangkan gejala klinis lainnya dianggap sebagai manifestasi sekunder. Kehilangan protein melalui urin menyebabkan terjadinya hipoalbuminemia. Penelitian ini bertujuan mengidentifikasi hubungan antara proteinuria dan hipoalbuminemia pada anak dengan sindrom nefrotik. Metode yang digunakan adalah studi retrospektif dengan desain Cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…NS in children is the most commonly found disease of the child's kidneys [10], [11]. NS is a clinical syndrome with symptoms of massive proteinuria (≥40 mg/m 2 LPB/h or protein/creatinine ratio in urine while >2 mg/mg or dipstick ≥2+), hypoalbuminemia ≤2.5 g/dL, edema, and can be accompanied by hypercholesterolemia [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NS in children is the most commonly found disease of the child's kidneys [10], [11]. NS is a clinical syndrome with symptoms of massive proteinuria (≥40 mg/m 2 LPB/h or protein/creatinine ratio in urine while >2 mg/mg or dipstick ≥2+), hypoalbuminemia ≤2.5 g/dL, edema, and can be accompanied by hypercholesterolemia [2].…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis of NS in patients under 1 year and above 8 years of NS should be performed renal biopsy before obtaining immunosuppressive therapy including steroids, because at this age the incidence of NS is an idiopathic type [8]. About 50% of children affected by NS are 1 year 6 months to 5 years old; 75% are younger than 10 years old [11], [12]. This was different in our study where the median age in this study was found at age 10 in the SRNS group and the average age of 12.5 years in the SSNS group.…”
Section: Figure 1: Systolic Blood Pressure Boxplot Chart In Steroid-resistant Nephrotic Syndrome (Ns) and Steroid Sensitive Ns Groupsmentioning
confidence: 99%
“…Sekitar 47,3% penderita sindrom nefrotik memiliki proteinuria  3+ dan 52,7% memiliki proteinuria <3+ [29]. Sekitar 71,4% penderita sindrom nefrotik lebih banyak memiliki proteinuria 3+, diikuti proteinuria 2+ sebanyak 25% dan proteinuria 1+ sebanyak 3,6% [32]. Proteinuria memicu terjadinya penurunan kadar albumin atau yang disebut hipoalbuminemia.…”
Section: Secang (Caesalpinia Sappan L)unclassified